2012
DOI: 10.1186/1556-276x-7-237
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-long Pt nanolawns supported on TiO2-coated carbon fibers as 3D hybrid catalyst for methanol oxidation

Abstract: In this study, TiO2 thin film photocatalyst on carbon fibers was used to synthesize ultra-long single crystalline Pt nanowires via a simple photoreduction route (thermally activated photoreduction). It also acted as a co-catalytic material with Pt. Taking advantage of the high-aspect ratio of the Pt nanostructure as well as the excellent catalytic activity of TiO2, this hybrid structure has the great potential as the active anode in direct methanol fuel cells. The electrochemical results indicate that TiO2 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…For example, a series of Pt/TiO 2 heterogeneous catalyst with various Pt particle sizes was prepared and tested for low temperature CO oxidation [139]. The result indicated that the Pt/TiO 2 heterogeneous catalyst that resulted in superior activity at the weight percent of Pt in Pt/TiO 2 heterogeneous catalyst was 5.0%, with the complete conversion temperature being 120°C [141143]. …”
Section: Tio2: As Support In Heterogeneous Catalysismentioning
confidence: 99%
“…For example, a series of Pt/TiO 2 heterogeneous catalyst with various Pt particle sizes was prepared and tested for low temperature CO oxidation [139]. The result indicated that the Pt/TiO 2 heterogeneous catalyst that resulted in superior activity at the weight percent of Pt in Pt/TiO 2 heterogeneous catalyst was 5.0%, with the complete conversion temperature being 120°C [141143]. …”
Section: Tio2: As Support In Heterogeneous Catalysismentioning
confidence: 99%